INCORPORATING ENGLISH AS AN INTERNATIONAL LANGUAGE IN TEACHING MATERIALS OF LISTENING SKILL FOR FIRST-YEAR FAST-TRACK STUDENTS = KẾT HỢP TIẾNG ANH NHƯ MỘT NGÔN NGỮ QUỐC TẾ VÀO TRONG TÀI LIỆU DẠY NGHE DÀNH CHO SINH VIÊN NĂM NHẤT CHƯƠNG TRÌNH CHẤT LƯỢNG CAO - Nguyễn, Phương Anh (2020)
The spread of English on a global language has resulted in the emergence of a new paradigm of English language teaching, English as an International Language (EIL), which switches the focus from native models to communicative effectiveness and the equal status of all varieties of English and cultures. This emergence urges scholars, educators and teachers to reconsider the appropriate approach to design syllabus materials. In Vietnam, though the goal of communicative effectiveness in English language teaching (ELT) is acknowledged, EIL syllabus material design remains at the stage of exploring teachers’ and students’ perceptions of EIL. Little attention has been given to measure the extent to which EIL has actually been incorporated in teaching materials. This study aims to explore the perceptions of material developers regarding EIL incorporation in teaching materials and the actual extent of EIL integration in teaching materials within the scale of listening skill of the course 2B*, Fast-track program, Faculty of English Teacher Education. The results show that there exists a mismatch between the material developers’ appreciation of EIL incorporation and their modest practices of incorporating EIL in teaching materials. However, due to various shortcomings, the study asks for more related research regarding the incorporation of EIL to capture a big picture of EIL implementation.